Formulation and Safety Tests of a Wickerhamomyces anomalus–Based Product: Potential Use of Killer Toxins of a Mosquito Symbiotic Yeast to Limit Malaria Transmission - Alessia Cappelli; Consuelo Amantini; Federica Maggi; Guido Favia; Irene Ricci (Toxins, 2021)
Wickerhamomyces anomalus strain WaF17.12 is a yeast with an antiplasmodial property based on the production of a killer toxin. For its symbiotic association with Anopheles mosquitoes, it has been proposed for the control of malaria. In an applied view, we evaluated the yeast formulation by freeze-drying WaF17.12. The study was carried out by comparing yeast preparations stored at room temperature for different periods, demonstrating that lyophilization is a useful method to obtain a stable product in terms of cell growth reactivation and maintenance of the killer toxin antimicrobial activity. Moreover, cytotoxic assays on human cells were performed, showing no effects on the cell viability and the proinflammatory response. The post-formulation effectiveness of the killer toxin and the safety tests indicate that WaF17.12 is a promising bioreagent able to impair the malaria parasite in vector mosquitoes.